KRETERIA DESAIN FOTOBIOREAKTOR SISTEM AIRLIFT REACTOR - Arif Dwi Santoso; Abdil H.S; Diyono . (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Global warming has become an increasingly important issue around the world today due to the rise of anthropogenic greenhouse gases emission, which gives several negative impacts on human life. There are some techniques have been studied and assessed i.e. physical mechanism by injected CO2 to the geological formations, chemical mechanism with artificial tree technology and biological mechanism by increasing the primary production through iron enrichment in high nutrient-low chlorophyll (HNLC) waters as well as mixing of water column below the sea surface. Those technologies, which are well known as Carbon Capture Storage ‘(CCS) technology, are expected to be applied to reduce the oncentration of anthropogenic CO2 in the atmosphere and to minimize the global warming. The Center of Environmental Technology, Agency for the Assessment and Application of Technology (BPPT) will carry out a research concerning CO2 reduction by a phytoplankton culture in a photobioreactor in three years. The main objective of this research is to assess the CO2 uptake capability of tropical phytoplankton. In this paper, we would showed the creteria and design to assembly a photobioreactor esspesially a air lift photobioreactor. To improve performance photobioreaktor, the materials included design criteria and the dynamics of fluids in fotobioreaktor have to considered propoerly. Other the hand, the selection of the most productive species and selection of appropriate media and economically also important to be done. Keywords: global warming, creteria and design, greenhouse gas, air lift photobioreactor